2003
DOI: 10.1046/j.1440-1754.2003.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Background severity of asthma in children discharged from the emergency department

Abstract: We observed deficiencies in use of preventer medications, use of written asthma management plans and lack of parental knowledge in some children with established asthma who presented to an ED. There was also a large number of children who did not have frequent background symptoms or who presented with their first episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 23 publications
2
9
0
1
Order By: Relevance
“…18 For the ED visit, and taking into account use of controller medications, 83.6% of the children in our study met the criteria for persistent asthma. Scribano et al 25 reported that 51% of children with acute asthma presenting to an ED had persistent asthma, whereas Khan et al 26 noted that 13% of children discharged to home from an ED had persistent asthma. Our finding of a higher frequency of persistent asthma may be accounted for by regional differences, acute asthma severity, and different interpretations of national guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…18 For the ED visit, and taking into account use of controller medications, 83.6% of the children in our study met the criteria for persistent asthma. Scribano et al 25 reported that 51% of children with acute asthma presenting to an ED had persistent asthma, whereas Khan et al 26 noted that 13% of children discharged to home from an ED had persistent asthma. Our finding of a higher frequency of persistent asthma may be accounted for by regional differences, acute asthma severity, and different interpretations of national guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Children included in this study were those who were discharged from the Emergency Department of Sydney Children's Hospital with asthma between 16 October 2000 and 28 February 2002. The details of the cohort have been described previously 14 . Parents of 310 children, who were seen in the ED and were subsequently discharged home, completed an asthma control questionnaire, the Newcastle asthma knowledge questionnaire 15 and the Juniper caregiver's quality of life questionnaire 16 .…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of predefined subgroups was performed to compare the similarity of efficacy for age (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), sex (male/female), immunoglobulin E (р 130 IU, Ͼ 130 IU), family history of asthma, rhinitis history, and number of episodes in previous year (р 5, Ͼ 5). No significant differences were observed (Figure 2).…”
Section: Other Analysesmentioning
confidence: 99%